2014
DOI: 10.1038/npp.2014.269
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the 5-HT1A Serotonin Receptor in the Hippocampus Is Required for Social Stress Resilience and the Antidepressant-Like Effects Induced by the Nicotinic Partial Agonist Cytisine

Abstract: Nicotinic acetylcholine receptor (nAChR) blockers potentiate the effects of selective serotonin reuptake inhibitors (SSRIs) in some treatment-resistant patients; however, it is not known whether these effects are independent, or whether the two neurotransmitter systems act synergistically. We first determined that the SSRI fluoxetine and the nicotinic partial agonist cytisine have synergistic effects in a mouse model of antidepressant efficacy, whereas serotonin depletion blocked the effects of cytisine. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ The antidepressant-like effect of YL was blocked by antagonists of 5-HT 1A , dopamine D 1 , and GABA A receptors. It was reported that 5-HT 1A and dopamine D 1 receptors in the hippocampus are involved in the antidepressant-like effect and hippocampal cell proliferation 28,36,37 . In the future, it will be necessary to elucidate how the monoamine system is directly and/or indirectly involved in the stress response and hippocampal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ The antidepressant-like effect of YL was blocked by antagonists of 5-HT 1A , dopamine D 1 , and GABA A receptors. It was reported that 5-HT 1A and dopamine D 1 receptors in the hippocampus are involved in the antidepressant-like effect and hippocampal cell proliferation 28,36,37 . In the future, it will be necessary to elucidate how the monoamine system is directly and/or indirectly involved in the stress response and hippocampal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Although both the nicotinic antagonist mecamylamine and the low efficacy partial agonist cytisine can decrease c-fos activity in the amygdala (Mineur et al, 2007), it is not known where in the brain nAChRs are required to alter behaviors relevant to stress and depression. Many brain areas that receive significant ACh innervation, including hippocampus, prefrontal cortex, habenuala, IPN, ventral tegmental area, and nucleus accumbens/striatum (Leao et al, 2015;Mineur et al, 2013Mineur et al, , 2015Picciotto and Mineur, 2014;Polter and Kauer, 2014;Zhao-Shea et al, 2013 could be involved in nAChR-related mood regulation. We demonstrate here that the non-selective nAChR antagonist mecamylamine can induce antidepressant-like effects when infused locally into the amygdala, suggesting that nAChR signaling is critical for baseline neuronal activity in this brain region, and that decreasing nAChR activity in amygdala is sufficient for an antidepressant-like response.…”
Section: Discussionmentioning
confidence: 99%
“…CD1 mice were selected for aggressive behavior as described previously (Mineur et al, 2013(Mineur et al, , 2015. On the initial defeat day, each C57BL/6J mouse was placed into a CD1 aggressor mouse home cage.…”
Section: Behavioral Testingmentioning
confidence: 99%
“…Further, as mentioned above, both chronic nicotine and the nicotinic antagonist mecamylamine can facilitate serotonin transmission in the hippocampus, while the effects of monoamine depletion can be partially reversed by nicotine administration and can lead to changes in anxiety-like behavior in the elevated plus maze (File et al, 2000a; File et al, 2000b; Fu et al, 1998; Kenny et al, 2000). We recently found that serotonin depletion could prevent antidepressant-like effects induced by the nicotinic partial agonist cytisine in the forced swim and the social defeat tests, while the effects of serotonergic drugs could be potentiated by this nicotinic compound (Mineur et al, 2014). Thus, changes in nAChR signaling, and more specifically, decreasing nAChR activity, can facilitate monoamine transmission and this may mediate the ability of nicotinic drugs to alter depression-like behaviors.…”
Section: Introductionmentioning
confidence: 99%